Towards integrating public art in Malaysian urban landscape - Hasna, Mohd Fabian; Mohd Tahir, Osman; Baharuddin, Mohd Nasir (Universiti Putra Malaysia Press, 2012)
Public art is an art form that exists in public area for public view. It can be in the forms of sculpture, mural, sculpture fountain and even stabile or mobile inside shopping mall. Its existence breaks the mundane environment and engages some kind of social flux towards public spaces. As urban landscape serves as urban retreat place, it is a much boost of a better quality environment when art approach is becoming part of urban landscape components. Seeing that the combination of site, art and people as one organization, it generates the aura of sustainability towards the urban landscape. However, a paradox situation happens in Malaysia as all the components function solely as different units. This paper focuses on an investigation on the potentials and issues of public art in Malaysian urban landscape. Literature review, document analysis and interview were also done to help justify the findings of the investigation. The first part of the paper examined public art as a contributor towards quality urban living environment. Subsequently, issues and problems which shield the Malaysian urban landscape and to be fully integrated by public art will be highlighted as well. It is argued that the process which artworks fusing with the urban landscape leads to an awareness and an understanding of the public issues to the notion of public art. Therefore, this paper will help to generate the society’s awareness and understanding of the effort of integrating public art in the Malaysia urban landscape